Jurassic World. Rebirth [videorecording (Blu-Ray)] - Crichton, Michael, 1942-2008 (Universal Studios and Amblin Entertainment, Inc., 2025)
"A new era is born in the iconic Jurassic World series. We join a covert extraction team as they race to the most dangerous place on Earth, an island research facility where dinosaurs too deadly for the original Jurassic Park were left behind. Their mission: to recover DNA from three colossal dinosaurs and unlock a drug with miraculous benefits for humanity. However, in a terrain populated by perils, they come face-to-face with a shocking discovery that has been hidden from the world for decades."--